Recurrent Nausea and Vomiting in a Pregnant Woman with Chronic Marijuana Use - Hyunyoung G. Kim; Jeremiah Moon; Heather Dixon; Paul Tullar (Case Reports in Obstetrics and Gynecology)
Background. Cannabinoid hyperemesis syndrome is a condition characterized by chronic cannabis use and cyclic episodes of nausea, vomiting, and abdominal pain, relieved by compulsive bathing. The syndrome is likely to be underdiagnosed in pregnant women due to its similarity with hyperemesis gravidarum in the presentation. Case. We report a 20-year-old pregnant woman with multiple admissions for recurrent nausea and vomiting who was observed to be taking frequent hot showers. Without other identifiable causes, she was diagnosed with cannabinoid hyperemesis syndrome and managed with antiemetics and abstinence. Conclusion. Abstinence from cannabis use is highly recommended in pregnant women due to its potential harm in fetal development and stimulation of intractable nausea and vomiting. Recognizing the symptoms and proper history taking prompt early diagnosis, allowing timely and adequate treatment.